Personality assessmet: Implications of a social-cognitive theory of personality - Cervone, Daniel; Jencius, Simon; G. Shadel, William (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF